Assessment of pediatric surgical needs, health-seeking behaviors, and health systems in a rural district of Pakistan. - Saqib Hamid Qazi; Syed Saqlain Ali Meerza; Reinou S Groen; Sohail Asghar Dogar; Mushtaq Mirani; Muhammad Khan Jamali; Zahid Ali Khan; Zahra Ali Padhani; Rasool Bux; Imran Ahmed Chahudary; Arjumand Rizvi; Saleem Islam; et al. (Public Library of Science (PLoS), 2022)
Surgical conditions are responsible for up to 15% of total Disability-Adjusted Life Years (DALY) lost globally. Approximately 4.8 billion people have no access to surgical care and this studies aim is to assess the surgical disease burden in children under the age of five years. We used Surgeons OverSeas Assessment of Surgical Need (SOSAS) and Pediatric Personnel, Infrastructure, Procedures, Equipment, and Supplies (PediPIPES) survey tools in Tando Mohammad Khan (TMK). A set of photographs of lesions were also taken for review by experts. All the data was recorded electronically via an android application. The current surgical need was defined as the caregiver's reported surgical problems in their children and the unmet surgical need was defined as a surgical problem for which the respondent did not access care. Descriptive analysis was performed. Information of 6,371 children was collected. The study identified 1,794 children with 3,072 surgical lesions. Categorization of the lesions by the six body regions suggested that head and neck accounted for the greatest number of lesions (55.2%) and the most significant unmet surgical need (16.6%). The chest region had the least unmet surgical need of 5.9%. A large percentage of the lesions were managed at a health care facility, but the treatment essentially consisted of mainly medical management (87%), and surgical treatment was provided for only 11% of lesions. The health facility assessment suggested that trained personnel including surgeons, anesthetic, or trained nurses were only available at one hospital. Basic procedures such as suturing and wound debridement were only performed frequently. This study suggests a high rate of unmet surgical need and a paucity of trained health staff and resources in this rural setting of Pakistan. The government needs to make policies and ensure funding so that proper trained staff and supplies can be ensured at district level.